Vaginal Primary Malignant Melanoma: A Case Report - Octaviyana Nadia NS; Sukma Dewi Pawestri; Reyhan Aditya; Fara Vitantri Diah C; Chamim Chamim (Syntax Corporation, 2022)
Primary vaginal melanoma is an extremely rare gynaecological malignancy comprising less than 0.2% of all melanomas. Vaginal melanoma is a very rare and aggressive type of gynecologic cancer. To date there is very limited literature regarding this topic due to small number of cases. Primary malignant melanoma of the vagina usually occurs in women aged in their 60s or 70s, with the majority of patients being postmenopausal. Patients commonly complain of vaginal bleeding, vaginal discharge or a palpable mass. The gold standard of diagnosis is established by pathologic examination. Management of vaginal melanoma depends on its staging. In early disease, tumor can be removed by wide localized excision with tumor free margin 1-2 cm depending on Breslow depth. In advanced disease, a radical surgery in addition to adjuvant therapy (chemo-, radio-, or immunotherapy) is performed. Currently, there is no optimal treatment regimen for vaginal melanoma. We present a case report of a 49-years-old female with vaginal melanoma stage IVA with urethral involvement and inguinal lymph node infiltration. We decided to perform radical surgery consisting of total hysterectomy, vaginectomy and urethral augmentation with pedicle flap from ileum . Keywords: Readiness, challenge, ASN, teknologi, society 5.0